Team dynamics within quality improvement teams: a scoping review. (31st March 2018) - Rowland, Paula; Lising, Dean; Sinclair, Lynne; Baker, G Ross
Abstract: Purpose: This scoping review examines what is known about the processes of quality improvement (QI) teams, particularly related to how teams impact outcomes. The aim is to provide research-informed guidance for QI leaders and to inform future research questions. Data sources: Databases searched included: MedLINE, EMBASE, CINAHL, Web of Science and SCOPUS. Study selection: Eligible publications were written in English, published between 1999 and 2016. Articles were included in the review if they examined processes of the QI team, were related to healthcare QI and were primary research studies. Studies were excluded if they had insufficient detail regarding QI team processes. Data extraction: Descriptive detail extracted included: authors, geographical region and health sector. The Integrated (Health Care) Team Effectiveness Model was used to synthesize findings of studies along domains of team effectiveness: task design, team process, psychosocial traits and organizational context. Results of data synthesis: Over two stages of searching, 4813 citations were reviewed. Of those, 48 full-text articles are included in the synthesis. This review demonstrates that QI teams are not immune from dysfunction. Further, a dysfunctional QI team is not likely to influence practice. However, a functional QI team alone is unlikely to create change. A positive QI team dynamic may be a necessary but insufficient condition for implementing QI strategies. Conclusions: Areas for further research include: interactions between QI teams and clinical microsystems, understanding the role of interprofessional representation on QI teams and exploring interactions between QI team task, composition and process.